bZIP Transcription Factor UvATF21 Mediates Vegetative Growth, Conidiation, Stress Tolerance and Is Required for Full Virulence of Rice False Smut Fungus Ustilaginoidea virens - Liu Yueran; Qu Jinsong; Wang Yufu; Yin Weixiao; Luo Chaoxi (Rice Science, 2023)
bZIP proteins are widely distributed in eukaryotic organisms and regulate a diverse range of physiological processes. Several bZIP proteins have previously been identified in Ustilaginoidea virens. However, the biological roles of these bZIP proteins in this pathogen are still unknown. Here, one of these bZIP protein coding genes, UvATF21, was functionally characterized. Targeted deletion of UvATF21 resulted in reduced conidiation and pathogenicity despite of the increased vegetative growth. The deletion mutants also significantly decreased the sensitivity to osmotic and oxidative stresses. Interestingly, deletion of UvATF21 exhibited different performances to cell wall integrity stress. These results indicated that UvATF21 played crucial roles in vegetative growth, conidiation, stress response, and full virulence in U. virens.